Receiving news between traditional media and virtual networking platforms for the “ new audience” in Algeria - مريم نريمان نومار (International Journal of Social Communication, 2022)
This study seeks to reveal the representations of news coverage of traditional media among the new audience (audience2.0) in Algeria by receiving news in virtual platforms and traditional media and the relationship between them. A sample of Facebook users were involved in the study by responding to an electronic survey, the study had reached a set of results most important are: The characteristics of the new audience Influence the receiving way of news coverage by them. The audience tend to search for news’ details on the virtual platforms when the traditional media did not satisfy their needs. In addition, publishing some news on Facebook, for example, without covering it in the traditional media affects the credibility of the latter according to the respondents’ answers.